2005
DOI: 10.1038/sj.mp.4001731
|View full text |Cite
|
Sign up to set email alerts
|

A haplotype within the DISC1 gene is associated with visual memory functions in families with a high density of schizophrenia

Abstract: We have previously reported evidence of linkage and association between markers on 1q42 and schizophrenia in a study sample of 498 multiply affected Finnish nuclear families, leading to the recent identification of four significantly associated haplotypes that specifically implicate the Translin-Associated Factor X (TRAX) and Disrupted in Schizophrenia 1 and 2 (DISC1 and DISC2) genes in the genetic etiology of schizophrenia. Previously, the DISC genes were found to be disrupted by a balanced translocation (1;1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
93
2
3

Year Published

2007
2007
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(105 citation statements)
references
References 40 publications
(48 reference statements)
6
93
2
3
Order By: Relevance
“…21 Although originally reported as being undertransmitted to affected females, 21 it was later reported that in fact this haplotype is overtransmitted to affected males in this population. 22,23 Association of a haplotype overlapping HEP3 (called Hap 1) has further confirmed this finding in an independent study of North American schizoaffective patients. 24 However, in this population, the Hap 1 haplotype is reported to be undertransmitted to the affected individuals.…”
Section: Genetics Of Disc1 Discoverymentioning
confidence: 54%
See 1 more Smart Citation
“…21 Although originally reported as being undertransmitted to affected females, 21 it was later reported that in fact this haplotype is overtransmitted to affected males in this population. 22,23 Association of a haplotype overlapping HEP3 (called Hap 1) has further confirmed this finding in an independent study of North American schizoaffective patients. 24 However, in this population, the Hap 1 haplotype is reported to be undertransmitted to the affected individuals.…”
Section: Genetics Of Disc1 Discoverymentioning
confidence: 54%
“…2 A number of studies have since reported evidence of linkage or association between the DISC1 locus and impaired cognitive function in both schizophrenic and normal individuals (Table 1b, Figure 1a). 22,25,[35][36][37][38][39][40] These deficits are consistent with dysfunction in the dorsolateral prefrontal cortex (PFC) and the hippocampus.…”
Section: Disc1 Variation and Cognitive Abilitiesmentioning
confidence: 76%
“…65 Interestingly, this protein also interacts with 14-3-3 gamma which has been implicated in schizophrenia previously 66,67 and which also interacts with the disrupted in schizophrenia 1 protein strongly implicated in the disease. 68,69 Postsynaptic density and glutamatergic system implicated by findings Several proteins that were differentially expressed in this investigation, namely PACSIN, NF-L, DYN-I and septin 5, are involved in the function of the pre-and/ or postsynaptic density, and through these in NMDAregulated glutamatergic neurotransmission, strongly implicated in the pathophysiology of schizophrenia. 70,71 In addition, many of the susceptibility genes for schizophrenia to date have been shown to play a role in glutamate function.…”
Section: Discussionmentioning
confidence: 75%
“…Preliminary data show an association with DISC1 gene in families of schizophrenia probands (Hennah et al, 2005). Genome-wide data from 168 schizophrenia families suggested a locus for verbal learning and memory on 4q21.…”
Section: Yesmentioning
confidence: 87%